2018
DOI: 10.1016/j.cell.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Restriction Triggers Angiogenesis via GCN2/ATF4 Regulation of VEGF and H2S Production

Abstract: Summary Angiogenesis, the formation of new blood vessels by endothelial cells (EC), is an adaptive response to oxygen/nutrient deprivation orchestrated by vascular endothelial growth factor (VEGF) upon ischemia or exercise. Hypoxia is the best-understood trigger of VEGF expression via the transcription factor HIF1α. Nutrient deprivation is inseparable from hypoxia during ischemia, yet its role in angiogenesis is poorly characterized. Here, we identified sulfur amino acid restriction as a proangiogenic trigger,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
251
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 258 publications
(264 citation statements)
references
References 69 publications
11
251
1
1
Order By: Relevance
“…In fact, increased H 2 S was observed upon dietary MR. Because another precursor homocysteine was significantly increased (unexhibited), which was consistent with previous reports . Moreover, the increased H 2 S was contributed by the regulation of enzymes cystathionine γ‐lyase (CSE, i.e., CGL) . The model of the transmethylation and TSP was clearly shown by Hine et al .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In fact, increased H 2 S was observed upon dietary MR. Because another precursor homocysteine was significantly increased (unexhibited), which was consistent with previous reports . Moreover, the increased H 2 S was contributed by the regulation of enzymes cystathionine γ‐lyase (CSE, i.e., CGL) . The model of the transmethylation and TSP was clearly shown by Hine et al .…”
Section: Discussionsupporting
confidence: 88%
“…In addition, recently, Longchamp et al. reported that sulfur amino acid restriction triggers angiogenesis via GCN2/ATF4 regulation of VEGF and H 2 S production . In our result, the increased of CSE enzyme activity, mRNA expression, protein level, and H 2 S concentration upon MR (Figure ) also provided the evidence of increased H 2 S upon dietary MR.…”
Section: Discussionsupporting
confidence: 82%
“…In the current study, we examined the multi-tissue and systemic extent to which dietary restriction (DR), a well-studied anti-aging intervention (Fontana and Partridge, 2015), impacts H2S production capacity and the sulfhydromes in liver, kidney, muscle, brain, heart, and plasma. In addition, we hypothesized the H2S producing enzyme cystathionine γ-lyase (CGL), which is required for stress resistance and angiogenesis benefits of shortterm DR (Hine et al, 2015;Longchamp et al, 2018;Trocha et al, 2019), is partially required for baseline and diet-induced changes in tissue-specific sulfhydromes. We found H2S production is strongest in liver and kidney and primarily driven by CGL in these tissues, while other tissues had relatively weak H2S production independent of CGL.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their differences in subcellular localization, CGL, CBS, and 3-MST are differentially expressed and active in tissue-specific manners, with CGL contributing the majority of enzymatic H2S production in the kidney, liver, and endothelium (Kabil et al, 2011b;Longchamp et al, 2018;Yang et al, 2019). Lack of CGL expression and/or activity is attributed to hypertension (Yang et al, 2008), neurodegeneration (Paul et al, 2014), and the inability to properly respond to dietary and endocrine cues (Hine et al, 2015;Ishii et al, 2010;Kabil et al, 2011a;Longchamp et al, 2018;Nakano et al, 2015). Remarkably, it was recently found that increased CGL expression in liver is a hallmark of numerous dietary, genetic, hormonal, and pharmaceutical mouse models of extended lifespan and may serve as a molecular biomarker associated with longevity (Tyshkovskiy et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In the nutrition restriction or hypoxia conditions, one adaptive response is the formation of new blood vessels, which is termed as angiogenesis. A recent study found that the GCN2/ATF4 pathway regulates VEGF expression and angiogenesis upon SAA (sulfur amino acid) restriction in endothelial cells, and this process is independent of hypoxia or HIF1α (hypoxia-induced factor 1α) (Longchamp et al 2018). In addition to sensing signal amino acid deprivation, TORC1 and GCN2 respond to different dietary protein sources.…”
Section: Gcn2 a Master Regulator Of Amino Acid Restrictionmentioning
confidence: 99%